Pendampingan Pengelolaan Air Limbah Domestik di Lingkungan Kecamatan Pasar Rebo, Jakarta Timur - Herawati, Susetya; Kasman, Kasman; Artiani, Gita Puspa (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Domestic wastewater management in Pasar Rebo District, East Jakarta, is the focus of community service activities (P2M) carried out by the Urban and Regional Development Studies Study Program team in collaboration with the UNKRIS Civil Engineering Study Program. The aim of this activity is to increase community awareness and ability in managing domestic wastewater in their environment. The team provided technical guidance to improve the household wastewater management system and daily community behavior through FGD activities carried out for one day by inviting all leaders from sub-districts in Pasar Rebo District. Service methods include initial surveys, interactive discussions, and evaluations. The results noted a significant increase in residents' understanding and actions regarding wastewater management. The emphasis on active community participation strengthens the positive impact of this activity in creating a foundation for improving the quality of life to support the One Million Orchid Village program in Pasar Rebo District.